STRATEGI PEMASARAN DIGITAL PARIWISATA DI DESA WISATA SIGAPITON - Anggun Hardiyanti; Dewi Yanti; Muhammad Rizki Lubis (Jurnal Riset Multidisiplin Edukasi, 2025)
Sigapiton Tourism Village is a tourist destination located in the Lake Toba area with the main attractions of natural beauty and authentic local culture. This study aims to determine the effectiveness of the implementation of digital promotional media for Sigapiton Tourism Village through the AIDA (Attention, Interest, Desire, Action) model approach, and to analyze digital marketing strategies using SWOT analysis. The research used in this study is descriptive with a qualitative approach obtained through observation, interviews, and documentation. Data analysis was carried out descriptively and through SWOT mapping. The results of the study showed that the digital promotion carried out was quite effective in building attention, interest, desire, and some actions from the audience. Promotion strategies based on visual content, educational narratives, emotional approaches, and digital communication facilitation are the main strengths. Based on the SWOT analysis, the marketing strategy for Sigapiton Tourism Village is in Quadrant I (Strength-Opportunity), with an internal score of 0,02 and an external score of 0.20. This shows that the development of digital promotion can be directed at an aggressive strategy by utilizing internal strengths to maximize external opportunities.